IMPLEMENTASI PASAL 2 HURUF b PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA REPUBLIK INDONESIA NOMOR 8 TAHUN 2019 TENTANG STANDAR PENGELOLAAN DOKUMEN DAN INFORMASI HUKUM MELALUI WEBSITE JARINGAN DOKUMENTASI DAN INFORMASI HUKUM (JDIH) DI BIRO HUKUM SEKRETARIAT DAERAH PROVINSI RIAU - Dhea Inneke Putri; Mexsasai Indra; Zainul Akmal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The standard of management of legal documentation and information is still aseparate record for the Legal Bureau of the Riau Province Regional Secretariat. Themanagement of legal documentation and information is still not in accordance with Article2 Letter B of the Regulation of the Minister of Law and Human Rights Number 8 of 2019concerning Legal Documentation And Information Management Standards because themanagement of legal products on the Documentation and Legal Information Networkwebsite is still experiencing delays in updating legal products because the capacity forstoring legal products on the Legal Documentation and Information Network website isvery limited and results in the content or content of legal products cannot be publishedcompletely, therefore resulting in limited access for people in need.This research is classified as sociological legal research, namely research thatwants to look at the correlation between law and society with the gap between dass sollenand das sein.. The data sources used are primary data, secondary data and tertiary datawith data collection techniques using interviews and literature review.From the research results, there are three main things that can be concluded.First, the implementation of Article 2 Letter B of the Regulation of the Minister of Law andHuman Rights of the Republic of Indonesia Concerning Standards for Management ofLegal Documentation and Information in the Legal Bureau of the Regional Secretariat ofRiau Province can be said to have not run optimally due to delays in updating legalproducts, resulting in delays in updating the latest legal products on the website. JDIH.Second, supporting factors in the process of managing legal documentation andinformation at the Legal Bureau of the Regional Secretariat of Riau Province, namelyadequate facilities and infrastructure such as computers and the internet. Inhibiting factorsin the Riau Province JDIH management process include limited human resources in termsof the Riau Province JDIH management website, lack of guidance and budgeting for theRiau Province JDIH. Third, there is a virus on the JDIH Riau Province website. Third,regarding the efforts made, namely by adding human resources, increasing the budget andincreasing the database storage capacity of the Riau Province JDIH website.Keywords: Legal Documentation and Information Network – Management Standards –Legal Products